Screening Performance Characteristic of Ultrasonography and Radiography in Detection of Pleural Effusion; a Meta-Analysis - Yousefifard, Mahmoud; Baikpour, Masoud; Ghelichkhani, Parisa; Asady, Hadi; Shahsavari Nia, Kavous; Moghadas Jafari, Ali; Hosseini, Mostafa; Safari, Saeed (Archives of Academic Emergency Medicine, 2018)
Introduction:Â The role of ultrasonography in detection of pleural effusion has long been a subject of interest but controversial results have been reported. Accordingly, this study aims to conduct a systematic review of the available literature on diagnostic value of ultrasonography and radiography in detection of pleural effusion through a meta-analytic approach.Â Methods:Â An extended search was done in databases of Medline, EMBASE, ISI Web of Knowledge, Scopus, Cochrane Library, and ProQuest. Two reviewers independently extracted the data and assessed the quality of the articles. Meta-analysis was performed using a mixed-effects binary regression model. Finally, subgroup analysis was carried out in order to find the sources of heterogeneity between the included studies.Â Results:Â 12 studies were included in this meta-analysis (1554 subjects, 58.6% male). Pooled sensitivity of ultrasonography in detection of pleural effusion was 0.94 (95% CI: 0.88-0.97; I2= 84.23, p<0.001) and its pooled specificity was calculated to be 0.98 (95% CI: 0.92-1.0; I2= 88.65, p<0.001), while sensitivity and specificity of chest radiography were 0.51 (95% CI: 0.33-0.68; I2= 91.76, p<0.001) and 0.91 (95% CI: 0.68-0.98; I2= 92.86, p<0.001), respectively. Sensitivity of ultrasonography was found to be higher when the procedure was carried out by an intensivist or a radiologist using 5-10 MHz transducers.Â Conclusion:Â Chest ultrasonography, as a screening tool, has a higher diagnostic accuracy in identification of plural effusion compared to radiography. The sensitivity of this imaging modality was found to be higher when performed by a radiologist or an intensivist and using 5-10MHz probes.